1998
DOI: 10.1002/hep.510280301
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of proliferative cholangitis in a rat model with direct adenovirus-mediated retinoblastoma gene transfer to the biliary tract

Abstract: Proliferative cholangitis (PC) associated with hepatolithiasis develops the stricture of main bile ducts, and is the main cause of residual and/or recurrent stones after repeated treatments for hepatolithiasis. The aim of this study was to inhibit PC using the cytostatic gene therapy with direct adenovirus-mediated retinoblastoma (Rb) gene transfer to the biliary tract. PC was induced by introducing a fine nylon thread into the bile duct in a rat model. The adenovirus vector encoding a nonphosphorylatable, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
45
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 23 publications
6
45
0
Order By: Relevance
“…patchy necrosis, severe neutrophil and lymphocyte infi ltration, and marked bile ductular proliferation. These fi ndings are consistent with the biliary infection observed in other models [19,20] . Few cases of liver fi brosis occurred in this model, but repeated biliary infusions of E. coli would effectively induce recurrent cholangitis.…”
Section: Discussionsupporting
confidence: 82%
“…patchy necrosis, severe neutrophil and lymphocyte infi ltration, and marked bile ductular proliferation. These fi ndings are consistent with the biliary infection observed in other models [19,20] . Few cases of liver fi brosis occurred in this model, but repeated biliary infusions of E. coli would effectively induce recurrent cholangitis.…”
Section: Discussionsupporting
confidence: 82%
“…[3][4][5][6][7] Similarly, the use of viral and nonviral vectors for gene delivery to functionally compromised livers has been instrumental to establish 'proof of concept' in several experimental models. Various strategies involving adenoviral vectors have been used.…”
Section: Pared With Approximately 80% In Control Non-cirrhotic Liversmentioning
confidence: 99%
“…1,18 Calculi in secondary or tertiary subsidiary branches of bile duct are usually complicated with biliary duct stenosis. Therefore, even after successful stone clearance with choledochoscopy, stone recurrence is inevitable.…”
Section: Discussionmentioning
confidence: 99%
“…5,12 Fu-Yu li, Jing-Qiu Cheng et al 12 suggested that phenol is not only the most efficient sclerosants of gall bladder mucosa, but is also a powerful antiseptic which might not only assist in ameliorating biliary infection which commonly accompanies hepatolithiasis, but also could commendably destroy the biliary mucosa and induced fibrous conglutination in the bile duct lumen, leading to partial occlusion of the large-size and middle-size biliary ducts, and complete occlusion of the small biliary ducts. 18,22,23 However, the biliary system could not be permanently occluded by using phenol or ethanol alone due to the regeneration of biliary mucosa. 22 As an ideal liquid occlusion agent; cyanoacrylate, histoacryl or neoprene has such remarkable liquid-dynamic characteristics that could perfectly fill bile ducts of various sizes, including the acroteric branch.…”
Section: Discussionmentioning
confidence: 99%